2017
DOI: 10.1590/s1677-5538.ibju.2015.0479
|View full text |Cite
|
Sign up to set email alerts
|

Lateral decubitus position vs. lithotomy position: which is the best way to minimize patient’s pain perception during transrectal prostate biopsy?

Abstract: Introduction Considering the distinctive nature in terms of psychological stress and anal tone of position which is generally selected between lithotomy and left lateral decubitus (LLD), we postulated its effect on pain perception during biopsy, and investigated their association.Materials and Methods A prospective study for comparison of two biopsy positions which were perform in a different working day was conducted for 208 men (lithotomy position=86, LLD=122). The decision on the position was made solely ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The main factors related to pain during prostate biopsy were identified as age, procedure duration, prostate volume, and lithotomy position [6,[13][14][15]. Our results confirmed that age and procedure duration are associated with pain due to TRUS-guided prostate biopsy.…”
Section: Discussionsupporting
confidence: 75%
“…The main factors related to pain during prostate biopsy were identified as age, procedure duration, prostate volume, and lithotomy position [6,[13][14][15]. Our results confirmed that age and procedure duration are associated with pain due to TRUS-guided prostate biopsy.…”
Section: Discussionsupporting
confidence: 75%
“…Pain due to compression may also be caused by an extremely enlarged prostate and be attributable to the operator’s skill and experience as well. Finally, several studies reported differences in patients’ pain perception depending on the patients’ position (lateral decubitus vs. lithotomy) during TRUS-guided prostate biopsy 18 , 19 , 20 . However, the optimal position that minimizes pain remains controversial.…”
Section: Discussionmentioning
confidence: 99%